The Use of In Situ Behavioral Skills Training to Improve Staff Implementation of the PEAK Relational Training System. Issue 1 (2nd January 2016) - Belisle, Jordan; Rowsey, Kyle E.; Dixon, Mark R.
ABSTRACT: The study evaluated the effectiveness of an in situ behavioral skills training program for training 3 direct care staff to implement the Promoting the Emergence of Advanced Knowledge Relational Training System (PEAK) with 3 individuals with autism. PEAK is an evidence-based behavior analytic language development curriculum that uses discrete trials to promote the emergence of language. The data suggest that behavioral skills training improved staff implementation of PEAK and resulted in a corresponding improvement in selected language skills across 2 of 3 learners with autism.